Understanding thermal and electronic transport in high-performance thermoelectric skutterudites - Rogl, G.; Garmroudi, F.; Riss, A.; Yan, X.; Sereni, Julian Gustavo Renzo; Bauer, E.; Rogl, P. (Elsevier, 2022)
Fil: Rogl, G.. Universidad de Viena; Austria